Extensive Perirenal Hematoma Formation Following D-J Stent Insertion in a Solitary Functioning Kidney. Description of an Unusual Complication - Nomikos, Michael S.; Papanikolaou, Sarantis; Athanassopoulos, George; Koritsiadis, George (Highlights on Medicine and Medical Research Vol. 4, 2021)
Double-J ureteral stent insertion is a common urological procedure performed for the relief of renal obstruction either due to stone disease or genitourinary malignancy. A case of a 62-year-old woman who received D-J stent due to hydronephrosis of her solitary functioning left kidney and complicated with renal perforation and significant retroperitoneal hematoma formation is presented. She was managed conservatively with blood transfusion and double-J stent repositioning in the collecting system. Follow-up with noncontrast computed tomography (CT) of the abdomen was performed the first and third months after stent placement which showed stabilization of the hematoma. The hematoma was completely resolved 6 months post D-J reposition. Although a common procedure, ureteral stent placement is not without complications and a high clinical suspicion index is required for early diagnosis and proper management of poststenting renal hematomas. Close follow-up is very important to prevent hematoma-related complications.